PENERAPAN STRATEGI TAX PLANNING PADA PPh PASAL 22, PASAL 23/26 DAN PPh DALAM MENINGKATKAN EFISIENSI PAJAK BADAN - Putri, Rita Dwi; Wahyuni, Lili; Fitri, Dilla Ramadhani; Putri, Nadia Ananda; Sativa, Oriza; Putri, Puji Defani; Aini, Qurratun (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
In a competitive business environment, companies continuously seek ways to optimize financial performance, one of which is through effective tax management. Legitimate tax planning in compliance with tax laws and regulations serves as a vital instrument to minimize tax burdens and enhance after-tax profits. This article employs a literature review methodology by analyzing and synthesizing various studies, scientific journals, books, and other relevant publications that discuss the concept of tax planning, the mechanisms of Income Tax Articles 22, 23, and 26, as well as their relationship with Corporate Income Tax. The findings indicate that strategies such as selecting appropriate partners, utilizing tax facilities, managing transactions, and choosing suitable tax withholding methods can significantly reduce the tax credits of Income Tax Articles 22 and 23/26, ultimately contributing to greater efficiency in Corporate Income Tax payments. These strategies assist companies in managing cash flows and reducing the amount of tax payable at year-end. In conclusion, a comprehensive understanding and application of tax planning concerning withholding and collection taxes is a key factor in achieving legal corporate tax efficiency.